Health‐related quality of life in infants, toddlers and young children with sickle cell disease. Issue 1 (26th October 2021) - Houwing, Maite E.; Muntendam, Madieke J.; van Muilekom, Maud M.; Teela, Lorynn; Fijnvandraat, Karin; de Pagter, Anne P. J.; Heijboer, Henriëtte; van Oers, Hedy A.; Cnossen, Marjon H.; Haverman, Lotte
Abstract: Background: Little is known about health‐related quality of life (HRQoL) in young children with sickle cell disease living in a European country. Methods: A retrospective cross‐sectional evaluation of TNO‐AZL Preschool Children Quality of Life questionnaire (TAPQOL, 0–1 year) and Pediatric Quality of Life Inventory (PedsQL, 2–7 years) data was conducted. Study participants included caregivers of children with sickle cell disease aged 0–7 years attending the sickle cell centre at the Erasmus Medical Center or the Amsterdam University Medical Centers between April 2012 and October 2020. Comparisons were made with normative data on HRQoL in the general paediatric population. Results: The study enrolled 136 caregivers of 136 children. In children aged 0–5 years, no significant differences emerged between children with sickle cell disease and the general population. However, in children aged 5–7 years, children with sickle cell disease scored significantly lower on all subscales except for emotional functioning. Multiple regression models showed a negative association between age and HRQoL. No association was found between HRQoL and disease severity or sociodemographic characteristics. Conclusions: This study demonstrates that HRQoL is negatively correlated with age in young children with sickle cell disease with a significantly lower HRQoL in 5‐ to 7‐year‐olds when compared to the general population. Our study underlines the importance of measuring HRQoL in young children to identify patients with impaired HRQoL early in life in order to be able to intervene accordingly. Future research should focus on deepening the knowledge of factors influencing HRQoL in children with sickle cell disease.